Sufi Education According to The Shadhiliyya Method in The Islamic Society in Egypt and Indonesia: A Comparative Descriptive Case Study - Esmatt, Lamis; Haris, Abdul; Amin, Saiful (Journal of Educational Analytics, 2024)
Shadhili Sufi education in Islamic society in both Egypt and Indonesia differs greatly. Therefore, this study aims to clarify the objectives of Shadhili Sufi education and the method of Shadhili Sufi education, as well as apply the Shadhili Sufi education method in both Musala and Indonesia. The qualitative research was used as a comparative descriptive case study approach. The research respondents and informants were the directors of the mosque and the school, three teachers from each institution, and eight students from each institution to obtain the necessary data. The data collection method was interview, observation, and data documentation, and then the interactive analysis method was used. by Miles and Huberman, which took the form of data reduction/collection, data condensation, and conclusion. This indicated the existence of several differences and similarities between the goals, methods, and application of Shadhili Sufi education between Egypt and Indonesia.